Rive Gauche : Paris as a Site of Avant-garde Art and Cultural Exchange in the 1920s. - Mettinger-Schartmann, Elke (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2010)
From the late 19th century onwards Paris had been a congenial locus for bohemian life. By 1920 Montparnasse had superseded Montmartre as the intellectual and artistic heart of the city, inaugurating a decade of unequalled creative achievement and innovative self-performance. These were the years of the 'Roaring Twenties' or années folles . "Paris"--As Gertrude Stein famously remarked - "was where the twentieth century was". The Rive Gauche offered a carnivalesque atmosphere of liberality, where the manifold experiments of the avant-garde could breathe freely. This volume attempts to do justic.